IL-27-Induced Type 1 Regulatory T-Cells Produce Oxysterols that Constrain IL-10 Production - Vigne, Solenne; Chalmin, Fanny; Duc, Donovan; Clottu, Aurélie S.; Apetoh, Lionel; Lobaccaro, Jean-Marc A.; Christen, Isabelle; Zhang, Juan; Pot, Caroline (Frontiers in Immunology, 2017)
The behaviors of lymphocytes, including CD4+ T helper cells, are controlled on many levels by internal metabolic properties. Lipid metabolites have recently been ascribed a novel function as immune response modulators and perturbation of steroids pathways modulates inflammation and potentially promotes a variety of diseases. However the impact of lipid metabolism on autoimmune disease development and lymphocyte biology is still largely unraveled. In this line, oxysterols, oxidized forms of cholesterol, have pleiotropic roles on the immune response aside from their involvements in lipid metabolism. The oxysterols 25-hydroxycholesterol (25-OHC) and 7α,25-dihydroxycholesterol (7α,25-OHC) regulate antiviral immunity and immune cell chemotaxis. However their physiological effects on adaptive immune response in particular on various subset CD4+ T lymphocytes are largely unknown. Here we assessed oxysterol levels in subset of CD4+ T cells and demonstrated that 25-OHC and transcript levels of its synthesizing enzyme, cholesterol 25-hydroxylase (Ch25h), were specifically increased in IL-27-induced type 1 regulatory T (TR1) cells. We further showed that 25-OHC acts as negative regulator of TR1 cells in particular of IL-10 secretion via LXR signaling. Not only do these findings unravel molecular mechanisms accounting for IL-27 signaling but also they highlight oxysterols as pro-inflammatory mediators that dampens regulatory T cell responses and thus unleash a pro-inflammatory response.